PERANAN LEMBAGA AMIL ZAKAT NASIONAL BAITUL MAAL HIDAYATULLAH DALAM MENINGKATKAN KESEJAHTERAAN MUSTAHIQ KABUPATEN TULUNGAGUNG (IAIN Tulungagung, 2014)
The purpose of this study is to determine the role of the National Zakat Agency Baitul Maal Hidayatullah Tulungagung Mustahiq in improving welfare and to determine the constraints on zakat management conducted by the National Institute Amil Zakat Baitul Maal Hidayatullah Tulungagung. This study used interview and observation methods. The result of this study is the role of the National Institute Amil Zakat Baitul Maal Hidayatullah Tulungagung people in channeling funds are based on the 4 programs, giving endowments Qur’an, education by providing scholarships to disadvantaged children, the social construction of mosques and indigent compensation, as well as assistance of cattle, goats and catfsh.Keywords: Role of Zakat Institutions, Collection, Distribution, Baitul Maal Hidayatullah, Welfare of Mustahiq.